“Copwatching” and Rhetorical Work: Envisioning Sites and Scope of Participation in Public Writing - Michael Knievel (Reflections: A Journal of Community-Engaged Writing and Rhetoric, 2026)
Following Gogan (2014), this article outlines how shifting emphasis from persuasion to participation as the desired “end” of public writing can help scholars, teachers, and students better conceptualize public rhetorical work. To better understand the range of “participation,” I argue that scholars and teachers might consider three separate-but-overlapping formulations of public writing participation: 1) participation as confronting—accessing and inhabiting places of institutionally-sanctioned rhetoric through agonistic presence, 2) participation as conditioning and coordinating rhetorical action and engagement within broader ecologies, and 3) participation as constructing and creating through future-building and the assembling of publics. To describe these formulations, I outline the rhetorical work of “copwatching,” the organized effort to monitor policing through video documentation and other routinized tactics. Functioning within the contemporary ecology surrounding police reform, copwatching’s diverse activities help illustrate the realities of public rhetorical work as forms of strategic participation across times and spaces.